ON THE EXTRACTION OF INTRACELLULAR FREE AMINO ACIDS OF WINE YEAST AT MULTIPLE TREATMENT BY ETHANOL (Proceedings of the YSU B: Chemical and Biological Sciences, 2005)
An example of five species of wine yeast the possibility of maximum extraction of amino acids is shown in multiple treatment by hot ethanol, permissive to extract majority of aliphatic, dicarbonic, dibasic and aromatic amino acids.
Keywords: free aromatic amino acids; wine yeast; maximum extraction